Preservice teachers perceptions about the use of blended learning in a science education methods course - Özkan Yılmaz; Kathy L. Malone (Smart Learning Environments, 2020)
Abstract The purpose of this quantitative study was to determine the effectiveness of blended learning within the context of a science education methods course for early childhood elementary preservice teachers in Turkey. Elementary teachers historically fear science and avoid using it in their classes. This course was blended to allow the students to experience active science learning during face to face sessions. Student perceptions about their experiences in a blended methods course were collected using a previously validated survey. The data analysis of the post-test only survey research design demonstrated that students’ perceptions were positive towards the use of blended learning within their science education methods course. However, the analysis determined that students felt that certain technical aspects of the blended learning environment hindered their learning.